E-NOVEL PRODUKSI FILM PATI: KARAKTERISASI PRODUKSI FILM PATI DARI LIMA JENIS PATI BERBEDA - Rezekinta, Angelina; Kasim, Anwar; Syafri, Edi; Chaniago, Irawati; Ridwan, Firman (Universitas Andalas, 2023)
The process of producing starch film using the casting method required a significant amount of time to obtain the desired film product. Therefore, this study was conducted to reduce the production time required for the starch film. The study used five varieties of starch: bengkoang starch, talas starch, glutinous rice flour, wheat flour, and MOCAF flour. The process involved homogenizing the starch and glycerol mixture utilizing a stirrer, followed by heating using a microwave and a compression process to accelerate the evaporation of water in the starch film. For the final drying stage, samples that had gone through this process were dried using a cabinet dryer. The result showed that the developed method of starch film requires only 60 minutes of the time needed compared to conventional casting method, which usually takes 5-48 hours. Furthermore, it was observed that starch film production using glutinous rice flour resulted in the highest tensile strength.